Platelet surface expression of stromal cell–derived factor‐1 receptors CXCR4 and CXCR7 is associated with clinical outcomes in patients with coronary artery disease. (13th March 2015) - Rath, D.; Chatterjee, M.; Borst, O.; Müller, K.; Langer, H.; Mack, A. F.; Schwab, M.; Winter, S.; Gawaz, M.; Geisler, T.
Summary Background Surface expression of stromal cell–derived factor‐1 (SDF‐1, CXCL12) on platelets is enhanced during ischemic events and plays an important role in peripheral homing of stem cells and myocardial repair mechanisms. SDF‐1 effects are mediated through CXCR4 and CXCR7. Both CXCR4 and CXCR7 are surface expressed on human platelets and to a higher degree in patients with coronary artery disease (CAD) compared with healthy controls. In this study, we investigated the prognostic role of platelet CXCR4‐ and CXCR7 surface expression in patients with symptomatic CAD. Methods and results In a cohort study, platelet surface expression of CXCR4 and CXCR7 was measured by using flow cytometry in 284 patients with symptomatic CAD at the time of percutaneous coronary intervention (PCI). The primary combined end point was defined as all‐cause death and/or myocardial infarction (MI) during 12‐month follow‐up. Secondary end points were defined as the single events of all‐cause death and MI. We found significant differences of CXCR4 values in patients who developed a combined end point compared with event‐free patients (mean MFIAUTHOR: Please define MFI at first use. 3.17 vs. 3.44, 95% confidence interval [CI] 0.09–0.45) and in patients who subsequently died (mean MFI 3.10 vs. 3.42, 95% CI 0.09–0.56). In multivariate Cox regression analysis, lower platelet CXCR4 levels were independently and significantly associated with all‐cause mortality (hazard ratio 0.24, 95% CI 0.07–0.87) and the primary combined end point of all‐cause death and/or MI (hazard ratio 0.30, 95% CI 0.13–0.72). Conclusion These findings highlight a potential prognostic value of platelet expression CXCR4 on clinical outcomes in patients with CAD.